2013
DOI: 10.5901/mjss.2013.v4n6p691
|View full text |Cite
|
Sign up to set email alerts
|

Economic Diversification in Nigeria: Any Role for Solid Mineral Development?

Abstract: For over four decades, the Nigerian economy has mostly depended on proceeds from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…From the analysis, the study found that non-oil gross domestic product, non-oil export and investment impacted positively on economic growth, but it was only the impact of non-oil gross domestic product was statistically significant within the period of analysis. This finding corroborates the outcomes of studies (Ayodele et al, 2013;Eko et al, 2013;Evbuomwan, 2016), that increased non-oil output is critical in the diversification of the Nigerian economy. It means, therefore, that any policy aimed at diversifying the economy must consider avenues for increasing productivity in the other sectors of the economy.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…From the analysis, the study found that non-oil gross domestic product, non-oil export and investment impacted positively on economic growth, but it was only the impact of non-oil gross domestic product was statistically significant within the period of analysis. This finding corroborates the outcomes of studies (Ayodele et al, 2013;Eko et al, 2013;Evbuomwan, 2016), that increased non-oil output is critical in the diversification of the Nigerian economy. It means, therefore, that any policy aimed at diversifying the economy must consider avenues for increasing productivity in the other sectors of the economy.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…In another study, Ayodele, et al (2013) identified the failure of past government solid mineral policy as well as previous government involvement in solid mineral exploration, as major setbacks in the growth and development of the solid mineral sector. He, therefore, suggested government action in the form of creating a conducive and socioeconomic environment which would facilitate both domestic and foreign investment in the solid minerals sector.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Similarly, it has been established that non-agricultural activities such as small-scale stone quarrying has the potentials of creating employment to 80% of the African population, as well as income to 30-50% of households in Sub-Saharan Africa and Asia [2]. However, inspite of the critical role that smallscale stone quarrying plays in the socioeconomic development of nations, the discovery and exploration of crude oil in Nigeria has atomized other important sectors of the Nigerian economy such as solid minerals with attendant declined contribution to Gross Domestic Product from 5.62% in 1980 to 0.16% in 2007 [3,4]. As a matter of fact, with the Nigerian economy coming out of recession and the clamour to diversify the economy becoming the new mantra of President Buhari's administration, preliminary observations show that youths in Zamfara State have keyed into this new agenda.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria was reported the largest producer of columbite at a time and the sixth largest producer of cassiterite at that time. Sixty minerals were estimated to be deposited on the African soil while Nigeria is endowed with forty-four of these sixty [1]. However, with the discovery of crude oil, less attention was paid to the solid mineral sector and the industry has since being in the state of comatose.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the discovery of crude oil, less attention was paid to the solid mineral sector and the industry has since being in the state of comatose. The effect of the neglect of the solid mineral sector was not that felt until recently when the revenue from the crude oil plummeted after a drastic fall in the selling price of Brent crude [1].…”
Section: Introductionmentioning
confidence: 99%